Public Satisfaction with The Performance of The Government of Joko Widodo – Jusuf Kalla - Hamed Norallah Bakheet (Jurnal Audience: Jurnal Ilmu Komunikasi, 2022)
AbstractOne of the parameters of leadership success is the public's satisfaction with the performance. The pair of President and Vice President Joko Widodo - Jusuf Kalla who led Indonesia in 2014-2019 also did not escape this assessment. Public voices can be used as an evaluation of the government that has been carried out for the future to formulate policies that can protect and side with the people. Based on this, the purpose of the research was to determine the extent of the public's response to the performance of the Jokowi-JK government, as well as which sectors were considered good or not by the public. This research uses mixed methods with a descriptive approach. The theory used is the concept of Governments, Performance Theory, Political Communication, and Community Satisfaction. Primary data was obtained using a questionnaire distribution technique to respondents, with a simple random sampling technique. Meanwhile, secondary data were obtained through literature studies relevant to this topic. The results showed that the economic and law enforcement sectors had a low level of satisfaction with Jokowi-JK's performance, namely 30% and 40%, respectively. Meanwhile, the social welfare sector and the political and security sector have a high level of satisfaction at 80%.